40Ar–39Ar biotite age of a lamprophyre dyke and constraints on the timing of ductile deformation inside the Idefjorden terrane and along the Mylonite Zone, Sveconorwegian orogen, south-west Sweden. (2nd April 2016) - Wahlgren, Carl-Henric; Page, Laurence; Kübler, Lutz; Delin, Hans
Abstract : A sharply cross-cutting lamprophyre dyke inside the Idefjorden terrane and along the Mylonite Zone in the Sveconorwegian orogen, Sweden, yields a plateau 40 Ar– 39 Ar biotite age of 914.6 ± 1.2 Ma. This result confirms a published K–Ar age and is interpreted to record magmatic intrusion of the dykes. The lamprophyres are coeval to the similarly oriented but less potassic 916 ± 11 Ma noritic to anorthositic Hakefjorden Complex exposed west of the Göta Älv Shear Zone in the Idefjorden terrane. The lamprophyres are characterized by high magnetic susceptibility, chilled margins, biotite phenocrysts and deuteric alteration of the groundmass. They classify as kersantite and minette, and are interpreted to represent rare, minor explosive mantle-derived magmas, intruded along deep-reaching, east-west trending, extensional structures related to the waning stages of the Sveconorwegian orogeny. Since the host bedrock, at the current level of erosion, was responding to brittle deformation prior to the intrusion of the lamprophyre dykes, the age of 914.6 ± 1.2 Ma sets a minimum limit for the termination of Sveconorwegian ductile deformation inside the Idefjorden terrane and along the Mylonite Zone, north of Lake Vänern. This contrasts to the situation in the westernmost Rogaland–Vest Agder sector of the Sveconorwegian orogen, in Norway, where 930–920 Ma anorthosite to granite plutonism was spatially related to high temperature-low pressure metamorphism and ductile deformation during the waning stages of the Sveconorwegian orogeny. The new age underscores the diachronic exhumation of the orogen.